BEHIND THE EXHAUSTION: EXPLORING CONTRIBUTING FACTORS TO BURNOUT AMONG UNIVERSITY STUDENTS - Vieryal Afrilia; Geminastiti Sakkir; Fitri Radhiyani (International Journal of Business English and Communication, 2025)
The purpose of this research is to explore the factors contributing to student burnout. This study employed a qualitative approach involving 10 participants from students in the English Education Study Program at UNM. Data were collected through self-report instruments and semi-structured interviews to gain a deeper understanding of the students' experiences with burnout. The findings revealed that several factors, such as academic workload, lack of control, insufficient support, and unclear goals, contributed to feelings of burnout. These insights highlight the importance of addressing burnout in educational settings to support students' well-being and academic involvement.